Parboiled rice bran in japanese quail diets at growing phase and residual effect at laying period - Freitas,Ednardo Rodrigues (2013)
Rice is the second largest cereal crop in the world and the by-products resulting from rice processing for human consumption are potential feedstuffs to compose poultry diets. In this sense, it was evaluated the influence of parboiled rice bran (PRB) in diets for Japanese quails in growing phase on the performance and digestibility, besides of residual effects and characteristics of egg quality in laying phase. A total of 324 Japanese quails with 7 days of age were distributed in a completely randomized design, with 6 treatments and 6 replicates of 9 birds. The treatments consisted of 6 isonutritives diets, being a control diet without PRB and the others containing 5, 10, 15, 20 and 25%. At the end of growing phase the birds were allotted in cages and fed the same diet without PRB at laying phase. At growing phase, the inclusion of PRB up to 5% promoted linear reduction in dry matter and gross energy digestibilities of diet; however a linear increase in metabolizable energy was noted. Feed intake, weight gain and final weight were reduced but not altering feed:gain ratio and body composition. At laying phase, the inclusion of PRB increased the age at first egg production but no influence was verified at age to reach 50% of egg production. No effect was verified at laying percentage, feed intake, weight and egg mass and feed:gain ratio. In economical evaluation, the inclusion of up to 25% of parboiled rice bran provided best economical indexes. The inclusion of PRB Japanese quails diets at growing phase can be recommended in levels up to 25%, without incurring future losses at laying phase.